Genome-wide development of SSR molecular markers for modern sugarcane cultivars - Xu, Yi; Chen, Siyuan; Chen, Shuqi; Wei, Xiangzhen; Shang, Heyang; Zhang, Qing; Zhang, Jisen (Frontiers in Plant Science, 2025)
Modern sugarcane cultivars are derived from interspecific hybridization between S. officinarum and S. spontaneum with complex genetic backgrounds, and their lack of SSR markers limits the genetic improvement of sugarcane. In this study, We searched for and identified SSR loci within the genomes of 14 Poaceae plants. Notably, a significant positive correlation (r = 0.958) was detected between genome size and the number of SSRs. We identified SSR loci in the whole genome of XTT22, a modern sugarcane cultivar. A total of 1,054,918 SSR loci were identified, with a frequency of 123 loci/Mb and an average of 1 SSR locus per 8.11 kb, with Chr1 having the highest content and frequency of SSR loci. Among different repeat types, the number of mononucleotide repeats (620, 901) and dinucleotide repeats (238, 261) was the largest, accounting for 81.45% of the total number of SSR loci, and the number of SSR decreases with the increase of the number of SSR repeat motifs. Based on the above SSR loci, 910,519 primer pairs were obtained, and 459 SSR markers with polymorphism were screened. The polymorphism rate of SSR markers among different SSR repeat types ranged from 81.97% to 97.90%, and the pentanucleotide repeat type had the highest number of SSR markers. In order to test the universality of the developed SSR markers in sugarcane and its related species, 24 polymorphic SSR markers were randomly selected for verification in 33 sugarcane and its related species and amplified 134 alleles in total. Each pair of primers amplified 1-11 alleles, with an average of 5.58 alleles per pair. This study is the first to systematically develop SSR molecular markers for modern sugarcane cultivars at the genome-wide level, which not only enriches the number of existing SSR markers of modern sugarcane cultivars, but also provides important molecular markers to support the molecular marker-assisted breeding of sugarcane.